SAT0765-HPR Criterion and concurrent validity of the american-english version of the flare questionnaire to detect and measure flares in rheumatoid arthritis. (15th June 2017) - Barroso, N; Woodworth, TG; Guillemin, F; Furst, DE; Brook, J; Kafaja, S; Borazan, N; Elashoff, DA; Fautrel, BJ; Ranganath, VK
Abstract : Background: Despite advances in rheumatoid arthritis (RA) therapeutic agents, difficulty in managing RA flares persists, and remission or the persistent absence of inflammation remains challenging to achieve. The French FLARE (F-FLARE) was developed to facilitate and standardize detection and measurement of RA flares between clinic visits. 1, 2 We have previously reported the cognitive debrief for the published British English version, which determined that revision of wording and presentation of items was required. Here we report validation of the American English version of FLARE (Am-E FLARE-RA). 3 Objectives: To assess whether the Am-E FLARE questionnaire performs comparably to the French version of FLARE in detecting RA flare in an American English-speaking clinic population. Methods: We enrolled patients attending UCLA rheumatology clinics. After informed consent, patients completed a questionnaire to collect demographics, Am-E FLARE, RAPID3, patient global visual analog scale (VAS), and self-reported flare at time of visit or between visits (yes/no). Questionnaires were provided to patients without specific instruction. From the electronic medical records, we extracted MD global VAS, MD-reported flare, seropositivity, disease duration, swollen/tender joint counts (SJC/TJC), and calculated the clinical disease activity index (CDAI). Analyses included Wilcoxon rank sum tests and Spearman correlations to assess criterion and concurrent construct validity. Results: Eighty-five RA patients diagnosed by the1987 American College of Rheumatology (ACR) criteria enrolled in our study. For the study population as a whole, mean age was about 50 years and most were female. Mean disease duration was about 10 years and about 65% were seropositive. (see Table). Am-E FLARE scores were significantly higher in patients' self-reporting flare compared to patients who reported no flare (p=0.005), and also for patients with MD-reported flare compared to those without flare (p=0.008) (see Table). Interestingly, there were no significant differences in SJC (p=0.82) and physician global (p=0.19) between patients who self-reported flare versus those who reported no flare. In addition, the Am-E FLARE scores correlated moderately with both CDAI (corr=0.46) and RAPID3 (corr=0.57). Conclusions: The Am-E FLARE is feasible for use in clinic, and shows good criterion validity, with scores significantly higher in patients who self-report flare. In addition, Am-E FLARE shows good discriminant validity, distinguishing patients who are flaring according to MD or patient self-report from those who are not. Finally, Am-E FLARE demonstrates construct validity comparable to that of the original French version of FLARE. References: Jean-Marie Berthelot, Michel De Bandt, Jacques Morel, et al. A tool to identify recent or present rheumatoid arthritis flare from both patient and physician perspectives: The "FLARE" instrument. Ann Rheum Dis 2012;71:1110–1116. Fautrel B, Morel J, Berthelot JM, et al. Validation of FLARE-RA, a self-administered tool to detect recent or current rheumatoid arthritis flare. Arthritis Rheumatol. 2016 Sep. 16. EULAR14-SCIE-4820. Disclosure of Interest: None declared